Review of the monograph: Telepen S.V. “The commander and his soldiers (Principate period). Military Leadership in Ancient Rome». Mozyr: MSPU named after M.P. Shamyakin, 2020. 196 p. - A. P. Belikov (Гуманитарные и юридические исследования)
.